PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 014 PUJUD - Oen Karolina; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research problem is in learning this knowlage social science (IPS student learning outcomes is still very low, there are still many students who are less able to infer the learning material, many students are passive, lazy student asked. It is very clear from these problems, students can not absorb the material well. Seeing these conditions need to be changes and improvements in learning process. Implementation Approach Contextual Teaching and Learning (CTL) to improve learning outcomes knowlage social science grade 1V SDN 014 Pujud on material economic activity and utilization of natural resources. Contextual Teaching and Learning (CTL) is a learning process that emphasizes the involvement of students in full process to be able to find a material that is learned by plugging in their lives. Subjects in this study were students of grade 1V SDN 014 Pujud with total of sixteen students. The study is in the form of classroom action research (PTK) was conducted in two cycles with two meetings and one repeat of the end of each cycle. Data collection instrument in this study is the observation sheet teacher activity, student activity observation sheet and repeat the test end of the cycle. IPS learning ability can be seen from the increase in base score with an average value of 66.87 with complete categories, the first cycle with an average value of 74.04 with the category is not exhaustive and the second cycle with an average value of 90.03 by category completely. Evident from the average yield basis, the first cycle and the second cycle must be increased. In the first cycle of 62.5% and has increased very significantly in the second cycle of 87.55%. The results of analysis of data obtained from the results of hypothesis conducted refer to standard completeness of student learning outcomes, and this means that the application of the approach Contextual Teaching and Leaning (CTL) is received and can improve learning outcomes IPS grade IV SDN 014 Pujud. Keywords: Learning Outcomes, IPS, Application of CTL approach